PENGARUH MANDATORY AUDITOR SWITCHING TERHADAP KUALITAS AUDIT - Adzra Fajriani; Tarmizi Achmad (Diponegoro Journal of Accounting, 2023)
This study aims to test and obtain empirical evidence on the effect of mandatory auditor switching on departing and replacement partners on audit quality. The variables used in this research are dependent variables consisting of audit quality, independent variables in the form of departing partner before mandatory switching and replacement partner before mandatory switching. Company size, financial leverage, profitability, and loss as control variables. The population are all companies in the food and beverage, textile, retail, construction, and electronic & electrical devices industries on the Indonesia Stock Exchange (IDX) for the period 2018 - 2021. Discretionary accruals and the name of the audit signing partner in that year used as the dataset. The data collection technique was carried out by purposive sampling method. The analysis method used to test the research variables is multiple linear regression analysis.The results of this study indicate that mandatory auditor switching on departing partner has a positive significant effect on audit quality. However, mandatory auditor switching on replacement partner has a positive but insignificant effect on audit quality.